'Fooling the Court of the Lord Pope': Dafydd Ap Llywelyn's Petition to the Curia in 1244. (1st December 2016) - Wiedemann, Benedict
Dafydd ap Llywelyn's approach to Pope Innocent IV in 1244 was classified as an attempt to become a papal 'vassal' by Michael Richter in an article of 1971. It seems more likely, however, both that Dafydd saw his relationship with the papacy as one of protectio, and that the precise form of the relationship was in fact incidental to his appeal. Dafydd took advantage of the routinization of papal administration to have local judges-delegate investigate Henry III's extorted treaties of 1241. The judges' appointment was not an acknowledgement by the papacy that Dafydd had a good case, or whether he was a papal 'vassal' or protégé.